The Effect of Low Impact Aerobic Exercise on the Physical Fitness of Elderly Gymnastics Members in the Lin Tien Kung Community, South Tangerang City - Bambang Suwito Kusumo Widagdo; Kevin Ramadhan; Gatot Sukartono; Fikra Azahra; M Hafid Qolbi; Ade Chandra Wiguna (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aimed to determine the effect of Low Impact Aerobic exercise on the physical fitness of elderly individuals in the Lin Tien Kung Exercise Community, South Tangerang City. The background of this study was based on the decline in physiological functions among the elderly and the limited availability of structured, safe, and age-appropriate exercise programs. This research employed a quasi-experimental method with a One Group Pretest–Posttest Design, involving 25 elderly participants as the sample. The exercise program was conducted over 8 sessions within 4 weeks, with a duration of 45–60 minutes per session, consisting of warm-up, main activity, and cool-down phases. Data were collected using the Senior Fitness Test (SFT), which includes six components of physical fitness: Chair Stand Test, Arm Curl Test, Chair Sit and Reach Test, Back Scratch Test, 2-Minute Step Test, and 8-Foot Up and Go Test. Data analysis was performed using the Paired Sample t-Test to identify significant differences between pretest and posttest results. The analysis results showed Sig. (2-tailed) values < 0.05 for all components, indicating a significant effect of Low Impact Aerobic exercise on improving elderly physical fitness. Low Impact Aerobic exercise was proven to be effective in enhancing muscle strength, flexibility, balance, and endurance, as well as providing psychological benefits in the form of increased motivation and social interaction. This study recommends the implementation of Low Impact Aerobic exercise as a regular activity for elderly communities to maintain health and improve quality of life sustainably.